Status Badan Usaha Milik Negara Terhadap Anak Perusahaan Holding Bumn - Iza Sadzili; Elisatris Gutom (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
: In line with the increasing role of BUMN in national development, especially in the success of Government programs assigned to BUMN as development agents and in order to face global economic developments, including the implementation of the ASEAN Economic Community, it is necessary to immediately increase the value, strengthen competitiveness, expand business networks, and independence of SOE management. Strategic steps to achieve this include strengthening the institutional and working mechanisms of BUMN and improving administrative order through improving the administration process. Institutional strengthening and working mechanisms of BUMN are carried out, among others, through the establishment of SOE holding companies. One of the Government's strategies in the formation of BUMN holding companies is by conducting State Capital Participation sourced from the shift of state-owned shares in certain BUMN and/or Limited Liability Companies to other BUMN and/or Limited Liability Companies. The formation of BUMN holding companies in its implementation has the potential to cause legal problems. The potential problems depart from the definition of BUMN as stipulated in Law Number 19 Year 2003 concerning State-Owned Enterprises. The potential problem raises two legal issues, namely related to the legal position of BUMNs that become subsidiaries in the Holding Company and the Authority of the State / Government in carrying out supervision and guidance functions to BUMNs that become subsidiaries in the Holding Company. The method of approach used is normative juridical and data obtained through literature study, namely library research on secondary data sources in the form of laws and regulations, namely Law Number 19 of 2003 concerning State-Owned Enterprises and Government Regulation Number 72 of 2016 concerning Amendments to Government Regulation Number 44 of 2005 concerning Procedures for Participation and Administration of State Capital in State-Owned Enterprises and Limited Liability Companies.